Storitve v mednarodnih ekonomskih odnosih - od izolacije k integraciji - Stare, Metka (Teorija in praksa, 2007)
Services have been a part of international economic relations for quite some time, nevertheless the modes and dimensions of their internationalisation have entered scientific research only after 1980. The article analyses the role of services in international economic relations since the beginning of the systematic research in the last quarter of 20th century and identifies the factors that fostered the expansion of services along with their contribution to deeper integration of services to international relations. It is being suggested that the inclusion of services into international trading system (WTO), the establishment of General Agreement on Trade in Services (GATS) and the progress in information-communication technologies were the most important drivers of services internationalisation. Along with those processes new actors emerged in international service transactions. Notwithstanding this acceleration services are still underestimated in international economic relations and not sufficiently explored, due also to non-transparency and multi-dimensionality of modes through which they enter international trade. It is being claimed in conclusion that to better understand and evaluate the role of services in international economic relations different actors should more thorougly apprehend various dimensions of international trade in services, its effects on national economy and on international economic relations.
Keywords: International economic relations; Mednarodni gospodarski odnosi; Services; Storitve; Liberalizacija; Liberalization; mednarodni ekonomski odnosi; mednarodna menjava